Does social software support service innovation? - Jenny Meyer (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2009)
Recent Internet technologies and web-based applications, such as social software, are being increasingly applied in firms. Social software can be employed for knowledge management and for external communication enabling access to internal and external knowledge. Knowledge in turn constitutes one of the main inputs to service innovation. Hence, social software has the potential to support service innovation. Using data from 505 German Information- and Communication Technology (ICT) and knowledge-intensive service firms, this is the first paper which empirically analyses the question whether the use of social software applications triggers innovation. Thereby, it refers to a knowledge production function in which social software use constitutes the knowledge sourcing activity. The results reveal that there is a positive relationship between social software and service innovation. Since this result is robust when controlling for former innovative activities and the previous propensity to adopt new technologies and to change processes, the analysis suggests that the causality runs from social software to innovation.
Keywords: O31; O33; M10; 330; Social software; web 2.0; service innovation; knowledge management; Social Software; Wissensmanagement; Innovationsmanagement; Dienstleistung; Unternehmensdienstleistung; Web 2.0; Deutschland